PROFIL PROTEIN BERBASIS SDS-PAGE PADA ULAT SAGU PENGASAPAN DENGAN DAN TANPA PENGGARAMAN - Alisha Triwahyuni; Ana Hidayati Mukaromah; Stalis Norma Ethica (Universitas Muhammadiyah Semarang, 2018)
Sago Larva (Rhynchophorus ferrugineus) is a high source of animal protein typical from Papua. One of weakness sago larva as foodstuff that is easily rot. To avoid decomposition can be done with fumigation and salting preservation. The purpose of this research is looking at the profile of protein fumigation with and without salting in sago larva. The method used is the method of Sodium Dodecyl Sulfat-Polyacrylamide Gel Electrophoresis (SDS-PAGE). Research sample used about 13 sago larva. One of sago larva used as a control without salting and fumigation, 6 of sago larva used time fumigation variation 2,4,and 6 minutes, than 6 of sago larva used time fumigation variation with salting at concentration 10% b/b. The results showed sago larva as a control has 31 protein bands different with band after fumigation with and without salting. Larva have been smoked for 2 minutes had 30 protein bands, for 4 minutes had 35 protein bands and for 6 minutes had 32 protein bands. While larva with salting and fumigation for 2 minutes has 29 protein bands, for 4 minutes has 22 protein bands and 6 minutes has 36 protein bands. These results indicate that amount of bands at sago larva are diverse because of different sample. The length time of fumigation then the higher level of the protein denaturation as marked with small value of molecular weight. Keywords: Fumigation, Salting, Sago Larva, SDS-PAGE